2020
DOI: 10.1038/s41598-020-57592-9
|View full text |Cite
|
Sign up to set email alerts
|

The Asthma-associated PER1-like domain-containing protein 1 (PERLD1) Haplotype Influences Soluble Glycosylphosphatidylinositol Anchor Protein (sGPI-AP) Levels in Serum and Immune Cell Proliferation

Abstract: Post-glycosylphosphatidylinositol (GPI) attachment to proteins 3, also known as PGAP3 or PERLD1 (PER1-like domain-containing protein 1), participates in the lipid remodeling process of glycosylphosphatidylinositol (GPI) anchor proteins during post-translational modification. Functional defect in PERLD1 was previously hypothesized to influence this process in T-cells and their subsequent activation and proliferation. This current study aims to functionally characterize PERLD1 genetic variants and relate this wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Studies have demonstrated multiple polymorphisms in ORMDL3 are associated with childhood asthma, regulate ORMDL3 transcript expression, and correlate with changes in T helper 2 cytokines levels [49, 50]. Our group has also identified significant asthma-associated eQTLs in ORMDL3, PPP1R1B, ZPBP2, and GSDMB [21], as well as characterized the functional roles of PNMT and PERLD1 genes in asthma [18, 19]. As it remains uncertain which gene or combination of genes is important in chr17q12-21, future studies in mice deficient in these candidate genes might provide further understanding on this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated multiple polymorphisms in ORMDL3 are associated with childhood asthma, regulate ORMDL3 transcript expression, and correlate with changes in T helper 2 cytokines levels [49, 50]. Our group has also identified significant asthma-associated eQTLs in ORMDL3, PPP1R1B, ZPBP2, and GSDMB [21], as well as characterized the functional roles of PNMT and PERLD1 genes in asthma [18, 19]. As it remains uncertain which gene or combination of genes is important in chr17q12-21, future studies in mice deficient in these candidate genes might provide further understanding on this question.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously identified 7 asthma-associated tag-single nucleotide polymorphisms (tag-SNPs) in the 17q12 locus that includes the PPP1R1B , STARD3 , PNMT , PERLD1 , and ERBB2 genes [17]. Of these genes, the functional roles of PNMT and PERLD1 genes in asthma have been previously characterized [18, 19]. However, the functional implications of ERBB2 SNPs in the pathogenesis process of asthma remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…PGAP3 (Post-GPI Attachment to Proteins 3) (also known as PERLD1 9 and PER1 12 ) is a chr:17q12-21 localized gene that encodes a glycosylphosphatidylinositol (GPI)-specific phospholipase that primarily localizes to the Golgi apparatus 12 , but can also be detected in the plasma membrane and cytosol (data from Human Protein Atlas v23.proteinatlas.org: https://www.proteinatlas.org/ENSG00000161395-PGAP3 ) 13 . PGAP3 encodes a seven-transmembrane protein in the Golgi that removes unsaturated fatty acids from the sn-2 position of GlycosylPhosphatidyliInositol (GPI) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The GPI anchor is formed in the ER, transported to the Golgi for fatty acid remodeling and cellular export to lipid rafts in the cell membrane 12,13 . The PGAP3 SNP 504 linked to asthma 9 has also been associated with peripheral blood mononuclear cell surface and secreted GPI-AP levels 9 , underscoring a potential mechanistic link between PGAP3, GPI-AP, and lipid rafts. Although there are no studies of the function of PGAP3 related to asthma, PGAP3 is known to regulate lipid rafts 14 that contain GPI-AP, receptors, adhesion molecules, signaling molecules, and enzymes of potential importance to asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first identification of GPI-anchored proteins (GPI-APs) [ 7 , 8 ], it has been speculated that this type of membrane anchorage could favor their spontaneous nonenzymic release from plasma membranes (see [ 9 , 10 ] for reviews). This has to be discriminated from the enzymic release, which has been amply documented in the past [ 11 , 12 ]. The possibility of spontaneous release was supported by the considerably lower forces of binding to and extraction from supported phospholipid/cholesterol mono- and bilayers for GPI-APs compared to transmembrane proteins as measured in various biophysical studies [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%